2019
DOI: 10.1016/j.chembiol.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Customizing Functionalized Cofactor Mimics to Study the Human Pyridoxal 5′-Phosphate-Binding Proteome

Abstract: Highlights d Enrichment of human vitamin B 6-binding proteins with cofactor-derived probes d In situ target screening of vitamin B 6 antagonists d Comparison of human cell lines suggests cell-typedependent cofactor loading states

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
0
17
1
3
Order By: Relevance
“…Size-exclusion chromatography (SEC) revealed that the protein independent of the presence of the affinity tag is predominantly dimeric even under reductive conditions excluding the role of disulfide bonds in this process (Figures 1A and S1A). 20 This observation differs ). 21 (D) Tandem MS (MS/MS) spectra identifying the PLP-binding site of PLPBP (K47) with corresponding score and posterior error probability (PEP; false discovery rate, FDR < 0.01).…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…Size-exclusion chromatography (SEC) revealed that the protein independent of the presence of the affinity tag is predominantly dimeric even under reductive conditions excluding the role of disulfide bonds in this process (Figures 1A and S1A). 20 This observation differs ). 21 (D) Tandem MS (MS/MS) spectra identifying the PLP-binding site of PLPBP (K47) with corresponding score and posterior error probability (PEP; false discovery rate, FDR < 0.01).…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…Plasma PLP is generally considered to be an effective diagnostic indicator of vitamin B6 status in humans . Due to its function in many biological metabolic pathways, PLP can be used as a biomarker to highly metabolic cells such as cancer cells, especially to metastatic cells . Therefore, PLP is demonstrated as a target molecule for tumors diagnosis, such as bladder, colon and breast cancers .…”
Section: Methodsmentioning
confidence: 99%
“…PLP‐dependent enzymes are evolutionary diverse, which makes its classification via sequence homology challenging. The group of Sieber has designed a pyridoxal analogue containing an alkyne click tag in the 2’‐position which is taken up by cells and phosphorylated to form the PLP analogue 36 (Figure 8), [53–54] which was accepted by PLP‐dependent enzymes, and by reduction with NaBH 4 led to the formation of stable conjugates. With this approach they could access 73 % of the current S. aureus PLPome and identified many more putative PLP‐dependent enzymes [53] .…”
Section: Activity‐based Protein Profiling Of Various Oxidoreductasesmentioning
confidence: 99%
“…With this approach they could access 73 % of the current S. aureus PLPome and identified many more putative PLP‐dependent enzymes [53] . Similarly, they could study the PLPome in human HEK293 cells and used it for target screening of Vitamin B 6 antagonists [54] …”
Section: Activity‐based Protein Profiling Of Various Oxidoreductasesmentioning
confidence: 99%